2005
DOI: 10.2116/analsci.21.833
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Powder Diffraction Patterns for Certain β-Lactam, Tetracycline and Macrolide Antibiotic Drugs

Abstract: X-ray powder diffraction (XRD) data for eight β-lactam viz., ampicillin sodium, ampicillin trihydrate, penicillin G procaine, benzathine penicillin, benzyl penicillin sodium, cefalexin, cefotaxime sodium and ceftriaxone sodium; three tetracyclines viz., doxycycline hydrochloride, oxytetracycline dihydrate and tetracycline hydrochloride; and two macrolide viz., azithromycin and erythromycin estolate antibiotic drugs were obtained using a powder diffractometer. The drugs were scanned from Bragg angles (2θ) of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 18 publications
3
22
0
2
Order By: Relevance
“…X-ray powder diffractometry (XRPD) can often be carried out to monitor structural changes in a solid with a high degree of accuracy in relation to conditions such as temperature, pressure or exposure to gaseous atmospheres of varying composition, including relative humidity [1][2][3]. XRPD is a useful qualitative tool in the pharmaceutical industry for studying the crystal morphology of active ingredients and polymers singly or in a mixture [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray powder diffractometry (XRPD) can often be carried out to monitor structural changes in a solid with a high degree of accuracy in relation to conditions such as temperature, pressure or exposure to gaseous atmospheres of varying composition, including relative humidity [1][2][3]. XRPD is a useful qualitative tool in the pharmaceutical industry for studying the crystal morphology of active ingredients and polymers singly or in a mixture [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…XRPD is a useful qualitative tool in the pharmaceutical industry for studying the crystal morphology of active ingredients and polymers singly or in a mixture [3,4]. Since the crystalline form of a drug is more rigid and thermodynamically stable than its amorphous form [5], it is usually necessary to study crystalline compounds alone and in composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19.04 • and 26.58 • , respectively. Thangadurai et al [41] has showed that the main characterizing peaks were at 19.41 • , 26.44 • , 26.86 • and 27.35 • . The crystallographic data (scattering angles, d-spacings, and relative intensities) for ciprofloxacin doped with iodine is listed in Table 5.…”
Section: X-ray Diffraction Investigationmentioning
confidence: 99%
“…In setting up the specimen and apparatus, co-planarity of the specimen surface with the specimen holder surface and the setting of the specimen holder at the position of symmetric reflection geometry were assured. The powders were passed through a 100 mesh sieve and were placed into the sample holder by the side drift technique (Thangadurai et al, 2003). In order to prepare a sample for analysis, a glass slide was clipped up to the top face of the sample holder so as to form a wall.…”
Section: X-ray Diffractometrymentioning
confidence: 99%